Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas Dan Produktivitas Terhadap Peringkat Obligasi Perusahaan - Dewi, Sofia Prima (Jurnal Ekonomi, 2013)
This study aims to obtain empirical evidence whether the company size, profitability, liquidity and productivity have an influence on corporate bond ratings. The samples are 77 companies listed in the data Indonesia Stock Exchange unless the company engaged in the banking sector and other financial institutions as well as issuing bonds stratified by PT PEFINDO during the years 2009-2011. Data analysis was performed with the help of a software program Statistical Product and Service Solutions (SPSS) for Windows version 16. The results showed that the profitability and liquidity have an influence on the company's bond rating firm while size and productivity having no effect on the bond rating companies.